2021
DOI: 10.3390/app11031083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2- and 3-Dimensional Cultured Periodontal Ligament Stem Cells; a Pilot Study

Abstract: This study compared the characteristics of periodontal ligament stem cells (PDLSCs) cultured using 3-dimensional (3D) versus conventional 2-dimensional (2D) methods. PDLSCs were cultured in either a 3D culture with a non-adhesive culture plate (Stemfit 3D®) or a conventional 2D culture using a 6-well plate. Morphology, viability, proliferation ability, and osteogenic differentiation were analyzed to characterize the differences induced in identical PDLSCs by 3D and 2D culture environments. In addition, gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…We clearly demonstrated that the 3D cultured spheroids of isolated PDLSCs were fully formed after 7 days of culturing in a non-adherent environment, and the viability of the cells in 3D cultured spheroids was confirmed at different time points of the spheroid formation. Our results contrast with the results reported by Jeong et al showing that the viability of PDLSCs in 3D culturing decreased compared to traditional 2D culturing ( 40 ). Besides, based on the culturing method, the spheroid morphology was preserved for 3 - 21 days, and the internal structure was homogeneous and biologically stable for at least 30 days ( 41 , 42 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We clearly demonstrated that the 3D cultured spheroids of isolated PDLSCs were fully formed after 7 days of culturing in a non-adherent environment, and the viability of the cells in 3D cultured spheroids was confirmed at different time points of the spheroid formation. Our results contrast with the results reported by Jeong et al showing that the viability of PDLSCs in 3D culturing decreased compared to traditional 2D culturing ( 40 ). Besides, based on the culturing method, the spheroid morphology was preserved for 3 - 21 days, and the internal structure was homogeneous and biologically stable for at least 30 days ( 41 , 42 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Human periodontal ligament (PDL) cell (CEFOgro™, Seoul, Korea) was cultured according to the manufacturer's protocol [17]. In brief, the cells were cultured in the growth medium containing 100 U/mL penicillin and 100 µg/mL streptomycin.…”
Section: Human Pdl Cell Culturementioning
confidence: 99%
“…Fourth, several prior studies on spheroid morphology involved observations over only 5-7 days. In the previous work of this research team, pPDLSCs were observed for 20 days to confirm their long-term stability [9]. However, the long-term stability of sPDLSC spheroids was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Periodontal ligament stem cells (PDLSCs) are easy to obtain and have a greater proliferation rate than bone marrow stem cells. PDLSCs are capable of differentiating into osteoblasts, cementoblasts, adipocytes, and chondrocytes, and can form a structure similar to periodontal ligaments in vitro [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%